Environmental drivers of mesocarnivores presence in Mediterranean landscapes - Alexandre, Marta Martins (2018)
Terrestrial ecosystems are highly complex and the species inhabiting them, including Humans, interact with each other influencing how each one exploits the available resources. With the growth of the human population and, consequently, of the urban areas and those devoted to produce goods for humans, the landscapes have undergone changes leading to an accelerated loss of habitat, which is considered the main cause for biodiversity decline. Due to this decline, species face challenges to their survival, shaping their ecology to adapt to new environmental conditions, and these adaptations have cascading repercussions throughout the ecosystem. Carnivores, being at high trophic levels, play an important role in the structure and proper functioning of ecosystems. The development and implementation of effective conservation plans is essential for the preservation of these species. Since they are mostly nocturnal and / or crepuscular, have high mobility and low densities, carnivores are usually monitored through the study of their signs of presence, in particular, their scats, because these are abundant and easy to find. In earlier studies, scats were exclusively identified through morphological and odoriferous criteria. However, due to the high uncertainty associated with this technique, new non-invasive sampling methods using molecular techniques began to be used, proving to be a solution for a more rigorous and accurate identification. The present study aimed: 1) to test the accuracy of mesocarnivores scats identification, from a community in the Northeastern region of Portugal, based on a conventional approach (morphological and odoriferous criteria), using as a standard for accuracy the results of molecular identification; 2) to understand, using the ecological modelling approach (GLMM), how the landscape context influences the presence of two generalist species - the red fox (Vulpes vulpes) and the stone marten (Martes foina) - in an area composed by natural areas and the practice of traditional agriculture. In total, between July and September of 2016, 291 mesocarnivores’ signs of presence (scats and footprints) were recorded. From this sampling, 63 scats were genetically analysed and the DNA of 83% of the samples was successfully amplified and sequenced. The highest success rate in species identification, based on morphological criteria, was 67%, but the success of the identification varied among species. Of the 291 recorded data and based on the observer's classification with the highest success rate, 212 signs of presence were considered to belong to the red fox and 55 to the stone marten. The generated distribution models revealed that the red fox appears to have two distinct strategies. When inhabiting an environment with a high percentage of forest, human activities have a negative effect (disturbance in habitat). Inversely, when in an environment where the forest cover is reduced, the presence of this species is positively influenced by the agricultural activity and the proximity to urban area (food availability). Stone marten’s distribution is negatively affected by anthropogenic activities (habitat alteration and disturbance), although the proximity to urban has a positive effect (allows to obtain food and avoids competition with other mesocarnivores). Our results support the need for the use of genetic identification as a tool in carnivore ecology studies, since it allows for a higher accuracy and provide more rigor to the morphological identification. We were also able to confirm the opportunistic nature and adaptability of the red fox and the stone marten. This study contributes to improve our knowledge of the dynamics and strategies of some of the most common mesocarnivores in Portugal, crucial for the application of conservation and management actions focused on those species. Furthermore, we demonstrated that, at least for the red fox, the landscape context influences the pattern of distribution. Consequently, by considering that populations of the same species are constrained by the same factors, independently of the landscape composition, will affect the efficacy of management measures put in place to assure the regional survival of a species